Surface Circulation and Vertical Structure of Upper Ocean Variability Around Fernando de Noronha Archipelago and Rocas Atoll During Spring 2015 and Fall 2017 - Costa da Silva, Alex; Chaigneau, Alexis; Dossa, Alina N.; Eldin, Gerard; Araujo, Moacyr; Bertrand, Arnaud (Frontiers in Marine Science, 2021)
Using current, hydrographic and satellite observations collected off Northeast Brazil around the Fernando de Noronha Archipelago and Rocas Atoll during two oceanographic cruises (spring 2015 and fall 2017), we investigated the general oceanic circulation and its modifications induced by the islands. In spring 2015, the area was characterized by lower SST (26.6°C) and deep mixed-layer (∼90 m). At this depth, a strong current shear was observed between the central branch of the eastward flowing near-surface South Equatorial Current and the westward flowing South Equatorial Undercurrent. In contrast, in fall 2017, SST was higher (∼28.8°C) and the mixed-layer shallower (∼50 m). The shear between the central South Equatorial Current and the South Equatorial Undercurrent was weaker during this period. Interestingly, no oxygen-rich water from the south (retroflection of the North Brazil undercurrent) was observed in the region in fall 2017. In contrast, we revealed the presence of an oxygen-rich water entrained by the South Equatorial Undercurrent reaching Rocas Atoll in spring 2015. Beside these global patterns, island wake effects were noted. The presence of islands, in particular Fernando de Noronha, strongly perturbs central South Equatorial Current and South Equatorial Undercurrent features, with an upstream core splitting and a reorganization of single current core structures downstream of the islands. Near islands, flow disturbances impact the thermohaline structure and biogeochemistry, with a negative anomaly in temperature (−1.3°C) and salinity (−0.15) between 200 and 400 m depth in the southeast side of Fernando Noronha (station 5), where the fluorescence peak (>1.0 mg m–3) was shallower than at other stations located around Fernando de Noronha, reinforcing the influence of flow-topography. Satellite maps of sea-surface temperature and chlorophyll-a confirmed the presence of several submesoscale features in the study region. Altimetry data suggested the presence of a cyclonic mesoscale eddy around Rocas Atoll in spring 2015. A cyclonic vortex (radius of 28 km) was actually observed in subsurface (150–350 m depth) southeast of Rocas Atoll. This vortex was associated with topographically induced South Equatorial Undercurrent flow separation. These features are likely key processes providing an enrichment from the subsurface to the euphotic layer near islands, supplying local productivity.